Biomonitoring of Acetylcholinesterase (AChE) Inhibitor and the Association with Hypertension among Farmers in Bandung, Indonesia - Mulyana Mulyana; Iwan Sugiarta; Lim Jen Fuk; Vani Nur Pratami; Dewi Yunia Fitriani; Nuri Purwito Adi; Dewi Sumaryani Soemarko (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: The use of acetylcholinesterase (AChE) insecticides is still widely used by farmers in flower and agricultural centers. However, biological monitoring of farmers is still very rare in Indonesia. AChE inhibitors are reported to have toxic effects on various organs.METHODS: This study involved 120 subjects in Cihideung, Cikole and Pangalengan areas. All subjects have been interviewed, physically examined and biological sample taken by medical team. Descriptive analysis was performed to assess general conditions of the subjects and AChE erythrocyte activity enzyme at pseudo-baseline and the next 3 months from pseudo-baseline. Statistical analysis have been performed of the pseudo-baseline AChE erythrocyte activity with hypertension and history of exposures.RESULTS: The median value of pseudo-baseline AChE erythrocyte activity was 8.10 (1.3-14.25) U/g hematocrit. In the comparison between pseudo-baseline and 3 month from pseudo-baseline AChE activity, 7 respondents from 19 respondents (36.84%) had lower enzyme activity than 70% and the others subjects have higher activity value. AChE erythrocyte activity is associate with frequency of insecticide exposures. AChE erythrocyte activity (p=0.04; Exp (B)=2.937 CI 95%=1.049-8.224) and age (p=0.025; Exp (B)=3.872 CI 95%=1.180-12.703) are independent risk factors for hypertension in farmworker.CONCLUSION: AChE erythrocyte activity associated with frequency of insecticide exposures and hypertension among farmworkers.KEYWORDS: AChE erythrocyte activity, frequency of insecticide expsoures, hypertension